Predictors of the resurgence and sustainability of open defecation-free status among adult residents in Kibwezi East Sub County, Makueni County, Kenya - Mutuku, Joshua M.; Juma, Joseph; W. Aidi, Bibianne (International Journal Of Community Medicine And Public Health, 2024)
Background: Worldwide, 2.4 billion persons lack improved sanitation and practice open defecation. In Kenya, about 14% of its population defecates in the open and the country loses over 324 million a year due to poor sanitation. The study focused on establishing infrastructural factors influencing the resurgence and sustainability of open-defecation-free status among adult residents in Kibwezi East Sub-County of Makueni County, Kenya. Methods: The study employed purposeful, cluster, proportionate, simple random sampling and descriptive cross-sectional design. Participants included residents aged 18 or older, who lived in the area at least two years. Chi-square tests at p≤0.05 examined relationships between independent and dependent variables. Results: Majority of respondents were Christian (98.8%), with 52.9% completing primary education. Most were female (68.6%), married (89.1%), and averaged 48.40 years. Education at or below primary level increased the likelihood of not sustaining ODF practices (uOR=1.567, 95% CI: 1.061-2.315, p=0.024). Sanitary facilities were often within 10-50 m (59.5%), with a median walk time of 3.0 min. ODF sustainability was less likely without user-friendly facilities (uOR=2.47, p<0.001) and with roofless toilets (uOR=0.355, p<0.001). Longer walking times (>3 min) reduced ODF sustainability (uOR=0.341, p<0.001). Absence of designated open defecation sites increased ODF odds by 1.669 times (UOR=1.669, p<0.001), and odor-free toilets enhanced sustainability (UOR=1.287, p=0.030). Conclusions: The results highlight the significance of socio-demographic factors, including education levels, and infrastructural in maintaining ODF status.